Evaluating and evolving a screening library in academia: the St Jude approach. Issue 4 (April 2021) - Nishiguchi, Gisele; Das, Sourav; Ochoada, Jason; Long, Heather; Lee, Richard E.; Rankovic, Zoran; Shelat, Anang A.
Highlights: Analysis of our current library identified gaps and opportunities for enhancement. We developed a 4-point strategy to build a screening library for the next decade. We document our efforts to develop a lead-like library with high scaffold diversity. Commercial libraries sample a small percentage of biologically relevant scaffolds. Libraries should be tailored to meet the demands of academic vs. industrial settings. Abstract : The quality of lead compounds is a key factor for determining the success of chemical probe and drug discovery programs. Given that high-throughput screening (HTS) continues to be a dominant lead generation paradigm, access to high-quality screening libraries is crucial for such efforts in both industry and academia. Here, we discuss the strategy implemented a decade ago to build from scratch one of the largest compound collections in academia, containing ∼575 000 carefully annotated small molecules, and a recent multidisciplinary effort designed to further enhance the collection to meet our research demands for the next decade.